Revealing The Relation between Global Capitalism and Television Industry - Aditya Yuli Sulistyawan; Eka Padmahantara Antonius (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2020)
The television industry is a broadcasting industry that requires much higher investment than other media. This is due to the need to provide broadcasting infrastructure, television technology that continues to grow, and because of the funding needs of the program. This need will become even bigger in line with increasing competition. The implication of these conditions is the creation of entry-barriers for independent investors with limited capital so that more likely to enter the market are large investors who have networks with broader business systems, which are very likely to initially be engaged in core businesses that are not related to the media. This paper is intended to reveal the relationship between global capitalism in the television industry which is increasingly troubling at the moment. The problem raised is how is the relation between the interests of global capitalism in the television industry in Indonesia? Such ownership patterns ultimately have an impact on broadcast content. Commercial television stations cannot be expected to present content that challenges policies that benefit large capital owners while harming labor interests. Thus, the tendency of the media to only present content that is not critical of capitalism cannot by itself be read as the fruit of the orders of the owners of capital or because of the ideology of media workers who are indeed pro-capitalism.